The Protean Character of the Modern Greek Man in the Work of Giorgos Theotokas: Euripides Pentozalis: The Parody of an Epic Persona - Νικολουδάκη Ελπινίκη (Education Sciences, 2024)
Giorgos Theotokas introduces a new character of modern Greek flaneur into prose of the so-called thirties’ generation. We can meet him in every place of the world, creating situations, from which he hopes to win glory and money. Business is his demon. He moves around exotic countries, selling his ideology, his genius, and cheap imitation of Ulysses.